Monitoring endoparasite status in sheep - Tekelye Bekele (International Livestock Centre for Africa, 1988)
Presents and discusses the purpose and experimental design of a study to be conducted on monitoring of endoparasite status in sheep. First phase will concentrate on monitoring endoparasites and productivity of Menz, Horro, Blackhead Somali and other breeds of highland sheep in their own habitat and second phase will compare the parasite burden and productivity performance of these breeds.